The impact of interventions to promote healthier ready‐to‐eat meals (to eat in, to take away or to be delivered) sold by specific food outlets open to the general public: a systematic review - Hillier‐Brown, F. C.; Summerbell, C. D.; Moore, H. J.; Routen, A.; Lake, A. A.; Adams, J.; White, M.; Araujo‐Soares, V.; Abraham, C.; Adamson, A. J.; Brown, T. J. (Obesity reviews, 2017)
Summary Introduction Ready‐to‐eat meals sold by food outlets that are accessible to the general public are an important target for public health intervention. We conducted a systematic review to assess the impact of such interventions. Methods Studies of any design and duration that included any consumer‐level or food‐outlet‐level before‐and‐after data were included. Results Thirty studies describing 34 interventions were categorized by type and coded against the Nuffield intervention ladder: restrict choice = trans fat law (n = 1), changing pre‐packed children's meal content (n = 1) and food outlet award schemes (n = 2); guide choice = price increases for unhealthier choices (n = 1), incentive (contingent reward) (n = 1) and price decreases for healthier choices (n = 2); enable choice = signposting (highlighting healthier/unhealthier options) (n = 10) and telemarketing (offering support for the provision of healthier options to businesses via telephone) (n = 2); and provide information = calorie labelling law (n = 12), voluntary nutrient labelling (n = 1) and personalized receipts (n = 1). Most interventions were aimed at adults in US fast food chains and assessed customer‐level outcomes. More ‘intrusive’ interventions that restricted or guided choice generally showed a positive impact on food‐outlet‐level and customer‐level outcomes. However, interventions that simply provided information or enabled choice had a negligible impact. Conclusion Interventions to promote healthier ready‐to‐eat meals sold by food outlets should restrict choice or guide choice through incentives/disincentives. Public health policies and practice that simply involve providing information are unlikely to be effective.